Exploring Family Lifestyle: How Families Embrace the Teachings of the Holy Quran in Firoz-Koh City, Afghanistan - Qassem Farhang; Sayed Shir Aqa Hashemi; Obaidullah Agheez (Journal of Asian Social Science Research, 2023)
The article delves into the family lifestyle through the lens of the Qur'an, employing a descriptive-analytical approach that integrates religious, moral, social, and intellectual dimensions with insights from sociology. It adopts a qualitative approach, employing structured individual interviews and narrative analysis as the primary methods of data collection. The research population comprises the families of Firoz-Koh City, with a sample size of 18 family members selected through random sampling. Information gathered includes the number of children, occupation, and age of marriage. Data analysis is conducted using theoretical coding techniques. The findings reveal the pivotal role of "lifestyle" as a fundamental aspect of human societies, encompassing various dimensions of human life. Furthermore, the Holy Quran, as a guiding force, emphasizes the importance of lifestyle in directing human behaviour. The Quran's comprehensive nature addresses humanity's needs for growth and perfection. This article highlights the significance of the family within the framework of the Holy Quran and identifies Quranic indicators of an ideal family lifestyle across religious, moral, social, and intellectual dimensions. Additionally, the study examines the detrimental factors hindering the pursuit of this Quranic lifestyle within families.